ARGUMENT CONSTELLATION IN JOURNAL ARTICLES: TOULMIN STEPHEN PERSPECTIVE (KONSTELASI ARGUMEN DALAM ARTIKEL JURNAL: PERSPEKTIF STEPHEN TOULMIN) - Yuliana Setyaningsih; R. Kunjana Rahardi (Jurnal Gramatika, 2020)
A constellation of arguments is present in each component of a journal article. Understanding the constellation of arguments in such journal articles is important because they will directly affect the writing of journal articles. This study aims to describe the constellation of arguments in the structure of the intended journal article. Data were collected by the observation method. The technique used in the framework of applying the method of referencing was a competent free observation technique. The next technique is note-taking. Data validation is done theoretically by confirming the available data on the theories. Also, validation is carried out to experts who master the matters of argument. The data validation was done after the data had been classified and verified. The data analysis method applied in this research is the method of distribution or distribution. The technique applied is a technique for direct elements.The data analysis method applied was the content analysis method. The results of the analysis were presented with informal presentation techniques. This research had produced the findings of the constellation of arguments in sections of journal articles. The parts of the journal article that may be present in the argument are in the following sections: (1) background, (2) literature review, (3) method, and (4) discussion. There is no argument in the conclusion section of the paper.